1972
DOI: 10.2134/agronj1972.00021962006400050008x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil pH on Element Concentration and Uptake by Maize: I. P, K, Mg, and Na1

Abstract: An understanding of soil‐plant relationships, plant nutrition, and fertilization requires a knowledge of the variability of the chemical composition and uptake of elements by plants. The availability of certain elements is related to soil pH and since many of the soils of the southeastern U. S. are acid, particularly in the subsoil, additional information is needed on the effects of soil pH on the growth, chemical composition, and uptake of elements by maize (Zea mays L.). Greenhouse experiments were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

1975
1975
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Trials carried out in the field have shown that the growth rate of maize declines with pH. A reduction of 40% has been observed when the pH is lowered from 6.1 to 3.9 for seven varieties of maize tested (Lutz et al 1972). This effect of pH is due to changes in the availability of ions in the soil rather than to any direct effect on the plant.…”
Section: Choice Of Mediamentioning
confidence: 90%
“…Trials carried out in the field have shown that the growth rate of maize declines with pH. A reduction of 40% has been observed when the pH is lowered from 6.1 to 3.9 for seven varieties of maize tested (Lutz et al 1972). This effect of pH is due to changes in the availability of ions in the soil rather than to any direct effect on the plant.…”
Section: Choice Of Mediamentioning
confidence: 90%
“…A quantidade dos micronutrientes necessária para promover um crescimento adequado é muito pequena, e a faixa de teores considerada adequada é muito ampla (JO-NES, 1972;LOCKMAN, 1969;NEUBERT et ai, 1969;LUTZ et al, 1972). A variação destes teores com os fatores ambientais, tais como, pH do solo e presença de outros íons, é elevada (WARNOCK, 1970;LUTZ et al, 1972;OLSEN, 1972); e a ocorrência de falhas na amostragem, preparação e análise química, são fatores que contribuem para tornar difícil a generalização sobre o comportamento dos cultivares. Em termos gerais, os cultivares apresentaram algumas diferenças em relação à acumulação de micronutrientes, embora estas não chegassem a merecer destaque especial.…”
Section: Acumulação De Micronutrientesunclassified
“…O aumento do pH do solo altera a disponibilidade de nutrientes, causando aumentos na absorção de N (Goodroad & Jellum, 1988), P, K, Ca e Mg (Lutz Jr. et al, 1972) pelo milho. São vários os trabalhos que demonstram aumentos consideráveis na produção de milho com a aplicação de calcário incorporado ao solo em sistema de preparo convencional (Gonzales-Erico et al, 1979;Camargo et al, 1982;Raij et al, 1983;Ernani et al, 1998).…”
Section: Introductionunclassified